Keterlibatan Mahasiswa Magang Kerja MBKM dalam Pelaksanaan Program Kerja di BLUD PT Syncore Indonesia - Putri, Maria Almaphym Cahya Kusuma (Universitas Methodist Indonesia, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) internship program provides opportunities for students to gain professional work experience while developing hard and soft skills. This article discusses the internship selection process, implementation, and results of student participation in the BLUD division at PT Syncore Indonesia. The internship activities included Unit Cost calculation, system trials, and performance report training for public health centers (puskesmas), article creation. This program equipped students with practical knowledge and improved their analytical and collaboration skills. This paper aims to inspire students and institutions in optimizing MBKM internship programs.